2014
DOI: 10.1128/jcm.01128-14
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Bacterial Load Assay Replaces Solid Culture for Measuring Early Bactericidal Response to Antituberculosis Treatment

Abstract: We evaluated the use of the molecular bacterial load (MBL) assay, for measuring viable Mycobacterium tuberculosis in sputum, in comparison with solid agar and liquid culture. The MBL assay provides early information on the rate of decline in bacterial load and has technical advantages over culture in either form.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 17 publications
4
69
0
Order By: Relevance
“…As a result, the multi-arm, multi-stage design resulted in a reduction in the final sample size of only 2%. A real-time biomarker such as the molecular bacterial load assay could overcome this problem by replacing culture allowing the endpoint results to be available rapidly 35 . Nevertheless, this was a crucial opportunity to assess the feasibility of this novel design in the context of an African multicentre infectious diseases clinical trial.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the multi-arm, multi-stage design resulted in a reduction in the final sample size of only 2%. A real-time biomarker such as the molecular bacterial load assay could overcome this problem by replacing culture allowing the endpoint results to be available rapidly 35 . Nevertheless, this was a crucial opportunity to assess the feasibility of this novel design in the context of an African multicentre infectious diseases clinical trial.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative approach includes quantification of abundant ribonucleic acid (RNA) species extracted from sputum as surrogate markers of bacterial clearance [32,33]. Honeyborne et al showed a high correlation between 16S ribosomal RNA (rRNA) with TTP in liquid media and CFUs on solid media over the first 14 days of treatment [34]. Although the half-life of messenger RNA (mRNA) and rRNA is significantly shorter than DNA in sputum, in the context of ongoing chemotherapy, it is unclear what proportion of m- and rRNA in expectorated sputum originates from dying bacteria.…”
Section: Pathogen Based Models and Biomarkersmentioning
confidence: 99%
“…In this respect, the MBL assay seem to be a better measurement as it detects ribosomal RNA that its decrease correlates better with the reduction of mycobacterial populations due to effect of chemotherapy. In addition, the data of the MBL assay are in good agreement when compared to both liquid culture (MGIT) and solid CFU measurements during a two-week EBA study (Honeyborne et al, 2014) as well as during current clinical trials (unpublished data).…”
Section: Measurement Of Patient Outcomementioning
confidence: 50%